Analysis of factors that influence consumers’ purchase intention of electric cars: Economic and business perspectives in emerging markets - Kusuma, Anak Agung Ngurah Abidzarr Dipo; Kusumastuti, Ratih Dyah (Journal of Economic, Business & Accounting Research, 2025)
Background: This study aims to determine the factors influencing consumer purchase intention for electric cars in Jabodetabek. Method: This quantitative research analyzes data collected from 150 respondents through surveys. The respondents in this study are individuals with knowledge of electric car products and reside in Jabodetabek. The data in this study were analyzed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) method. Finding: The results of this study indicate that attitude, perceived behavioral control, cognitive status, and monetary incentive policy significantly influence on purchase intention. However, subjective norm and product attributes do not show a significant influence. Conclusion: Additionally, the results of this study indicate that monetary incentive policy has the strongest influence on purchase intention. Novelty/Originality of this article: This study provides a novel insight into consumer purchase intention for electric cars in Jabodetabek by identifying monetary incentive policy as the most influential factor, while challenging the significance of subjective norms and product attributes.